Protective Efficacy of Recombinant Yersinia Outer Proteins against Bubonic Plague Caused by Encapsulated and Nonencapsulated Yersinia pestis - Andrews, G. P. (American Society for Microbiology, 1999)
To evaluate the role of Yersinia outer proteins (Yops) in conferring protective immunity against plague, six yop loci from Yersinia pestis were individually amplified by PCR, cloned, and expressed in Escherichia coli. The recombinant proteins were purified and injected into mice. Most Yop-vaccinated animals succumbed to infection with either wild-type encapsulated Y. pestis or a virulent, nonencapsulated isogenic variant. Vaccination with YpkA significantly prolonged mean survival time but did not increase overall survival of mice infected with the nonencapsulated strain. The only significant protection against death was observed in YopD-vaccinated mice challenged with the nonencapsulated strain.